FACTORS FOR NON-DONATION OF ORGANS AND TISSUES IN NEUROLOGICAL INTENSIVE CARE UNIT. - Santos, Shirlene Cerqueira dos; Dourado, Mavy Batista; Assis, Mineia Pereira da Hora; Silva, Mabel Olimpia Lima Silva; Santos, Raisa Noelia Sant'Ana Souza; de Souza, Anna Paula Lima (Revista de Pesquisa: Cuidado é Fundamental)
Objective: to identify the factors related to non-donation of organs and tissues in potential donors diagnosed with brain death, in a Neurological Intensive Care Unit. Method: descriptive, cross-sectional, retrospective, documentary study with a quantitative approach, of brain death protocols, from May 2017 to May 2020 and analyzed using the Statistical Package for Social Sciences program, version 22.0, using descriptive statistics. Results: 72 brain death protocols were completed, predominantly female (63.9%), brown (66.2%), aged 50 to 64 years (43.1%), described as the main cause subarachnoid hemorrhage (40.3%), with the outcome of non-effective donation (62.1%) and the main factor for non-donation to family refusal (45.7%). Conclusion: the need for greater investment in educational campaigns is emphasized, in order to reduce the rates of family refusal.